American Federation of Labor records - American Federation of Labor
Letterpress books containing correspondence of Samuel Gompers, and William Green, presidents of the American Federation of Labor (AFL), and other officials including James Duncan, Gabriel Edmonston, Frank K. Foster, and John McBride. Includes material pertaining to the formation of local unions, charters, bylaws, conduct of meetings, ethics, publicity, fund raising, arbitration, and boycotts. Subjects include the political principles of the AFL, communism, socialism, the anthracite coal strikes of 1897 and 1902, American Railway Union, International Association of Machinists, International Brotherhood of Teamsters, United Mine Workers of America, and The American Federationist, magazine of the AFL. Correspondents include Susan B. Anthony, Grover Cleveland, William Hugh Johnston, John L. Lewis, L.J. McGruder, P.J. McGuire, John Mitchell, John Morrison, Herman Robinson, Theodore Roosevelt, Daniel Joseph Tobin, Henry White, and Woodrow Wilson.
Microfilm edition of volumes 1-355 (volumes 251, 310, & 313 not received by the Library of Congress) available
Microfilm edition of volumes. 356-357 available
Microfilm produced from originals in the Manuscript Division.
Labor organization.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anthony, Susan B. -- 1820-1906 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Correspondence; Duncan, James, -- 1857-1928 -- Correspondence; Edmonston, Gabriel -- Correspondence; Foster, Frank K. -- 1854-1909 -- Correspondence; Gompers, Samuel, -- 1850-1924 -- Correspondence; Green, William, -- 1870-1952 -- Correspondence; Johnston, William Hugh, -- 1874-1937 -- Correspondence; Lewis, John L. -- 1880-1969 -- Correspondence; McBride, John, -- 1854-1917 -- Correspondence; McGruder, L. J. -- Correspondence; McGuire, P. J. -- 1852-1906 -- Correspondence; Mitchell, John, -- 1870-1919 -- Correspondence; Morrison, John, -- Esq. -- Correspondence; Robinson, Herman -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Tobin, Daniel Joseph, -- 1875-1955 -- Correspondence; White, Henry, -- 1866- -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; American Railway Union; International Association of Machinists; International Brotherhood of Teamsters; United Mine Workers of America; American federationist; Anthracite coal industry -- Pennsylvania; Anthracite Coal Strike, Pa., 1897.; Anthracite Coal Strike, Pa., 1902.; Arbitration, Industrial -- United States; Boycotts -- United States; Charters; Coal mines and mining -- United States; Communism; Fund raising -- United States; Labor disputes; Labor union meetings -- United States -- Planning; Labor unions -- Moral and ethical aspects -- United States; Labor unions -- Organizing -- United States; Labor unions -- Public relations -- United States; Labor unions -- United States -- By-laws.; Professional ethics -- United States; Publicity; Socialism; Strikes and lockouts -- Coal mining -- Pennsylvania